The latent causes of rework in floating production storage and offloading projects - Love, Peter E. D.; Edwards, David John; Irani, Zahir; Forcada, Nuria (Journal of Civil Engineering and Management, 2014)
There is growing demand for cost effective and reliable floating production systems to maximize marginal and new deepwater fields worldwide. Floating Production Storage and Offloading (FPSO) vessels are considered to be the most economical and viable options to meet this demand. Yet, FPSO projects are prone to significant cost and schedule growth. On average, FPSOs have been reported to experience a 20% cost growth and are delayed by six months. Overruns and delays represent uncertainties for owners, contractors and financial institutions. In-depth interviews with twenty-three practitioners about their experiences with FPSO projects revealed that rework arising from design and construction errors were major contributors to cost and schedule growth. Key latent conditions contributing to rework are classified according to people, organization and project. Using retrospective sensemaking an examination of the determinant histories in a new build and conversion FPSO that experienced rework was undertaken. The sharing of experience(s) is deemed pivotal for reducing rework in future projects, particularly through the use of communities of practice that are able to stimulate situated learning to take place. A reduction in rework will not only reduce cost and schedule growth, improve operational performance and augment safety.